Assessment of rice growers’ exposure to pesticides applied in Kelantan, Malaysia - Wong Hie Ling; Garthwaite David G.; Jais An Nurainee; Norman Nurul Najiah; Mohd Shobri Nurin Dalila; Brown Colin D. (BIO Web of Conferences)
There is a clear need for more information on occupational exposure to pesticides on smallholder farms in developing countries. This study investigates the exposure of rice growers to pesticides through the use of knapsack/backpack sprayers, a widespread practice in developing countries such as Malaysia. We collected pesticide application information from 23 rice growers using face-to-face interviews and questionnaires. We used the information to predict total daily exposure to individual active substances across a rice-growing season using selected exposure models. We then compared the estimates with toxicity thresholds to determine the potential risks. The 23 rice growers cultivated between 0.6 and 3.8 hectares of rice and applied pesticides on three and 13 spray days across the season, using up to eight active substances on individual days. Individuals had estimated average daily exposures to individual substances between 4.1x10-3 and 1.3x10-1 mg kg-bw-1 day-1, with dermal exposure accounting for 89 – 99.6% of total exposure. Overall, 28% of the 408 applications’ exposure exceeded the toxicity threshold. This was due to highly toxic pesticides and growers not wearing gloves while working. Health risks can be reduced by providing training and information on pesticide product selection and application practices.